Kajian Filologis Naskah Layang Carios Samud Kagungan Kraton Kacirebonan - Fika Hidayani (Indonesian Journal of Arabic Studies, 2019)
Philology is a medium to explore a classical scientific treasures. This knowledge had been studied because there are values contained in Â manuscripts that are still relevant to present life. These works are able to inform the thought, feeling, and information about various aspects of life that ever existed. One of the manuscript is Layang Carios Samud Kagungan Kraton Kacirebonan, which is from Cirebon. The manuscript is a translation from the Book of Hazar Masail that written in Persian (Iran) is a popular manuscript in the world in the Middle Ages, because it has been translated into various languages in the world. This manuscipt is expected be an additional reference in terms of religion for academics and the community.